Etheno-medicinal plant of Saputara Hill, Dang District, Gujarat. (International Journal of Scientific Research and Management (IJSRM), 2017)
Some plant used by human community to cure diseases and health related problems from long period of time are called etheno-medicinal plants. Saputara hill Dang forest is administered by Gujarat state forest Department (GSFD). The area lies between 200 30’ N latitude and 730 15’longitude. Saputara forest (120sq. km) is moist deciduous tropical type with an average rainfall 1200-1500mm. The mean temparature varies from about 80 c in winter to about 340 c in summer, with 30-80% humidity. The vegetation of this study area is of purely moist deciduous type with natural plants like Tectona grandis, Dendrocalamus strictus, Terminalia crenulata, T.bellerica, T.arjuna, Carrisa congesta and Accasia catechu in successive pattern. In conclusion, the medicinal species require special attention to conserve and documentation of their medicinal uses local people.